Influence of the practice of physical exercise and healthy eating on the Vigour of university lectures - Monserrat Hernández, Montserrat; Arjona Garrido, Ángeles; Checa Olmos, Juan Carlos; Casimiro Andújar, Antonio; Artés Rodríguez, Eva María; Salguero García, Darío (Frontiers in Sports and Active Living, 2023)
Introduction Vigour at work is characterized by high levels of energy and high desire to make an effort at work. This article is the result of a research carried out with university teachers in Spain whose main objective is to show what type and frequency of physical exercise and diet influence Vigour. Methods The sample consisted of 121 subjects, 62% of whom were women and 37.2% men. A questionnaire was administered to collect information on sociodemographic data, physical exercise habits, eating habits and Vigour at work. Cross-tabulations of the dimensions of Vigour with sex, age and type of contract offered were performed. Spearman correlations and Correspondence Analysis are also carried out to provide information on the intensity and type of relationships between the Vigour dimensions. Finally, the influence of the frequency of physical exercise and diet on Total Vigour is investigated. Results The results show that the relationships between the dimensions are very strong (sig = 0.001). In addition, the practice of moderate-high intensity physical exercise and maintaining a good adherence to the Mediterranean Diet is related to high levels of Total Vigour (F = 7.955; sig = 0.006). As for the influence of the sociodemographic variables used, significant differences were only observed in the Physical Strength dimension for sex (X2 = 6.173; p = 0.046) and age (X2 = 9.449; p = 0.051) and, with respect to the type of contract, in Emotional Energy (X2 = 19.487; p < 0.001). Discusión and conclusions The main conclusions of our study show that practicing physical exercise of medium-high intensity four hours or more per week and a high adherence to the MD is more related to high Vigour levels than just eating well or just practicing exercise. And more studies are needed on the influence of sociodemographic variables on Vigour and its different dimensions.